Research progress on hand hygiene of nursing students (护理实习生手卫生研究进展) - PENG Ling (彭琳); LEI Sai (雷赛); YANG Weiwei (杨微微); YU Lili (余丽丽) (中西医结合护理)
Hand hygiene is now regarded as one of the most important element of infection control activities in hospital. This paper reviewed the importance, current status and hospital management strategies on hand hygiene of nursing students, in order to provide a reference of hand hygiene management in healthcare settings. (手卫生是控制和预防医院感染最有效的手段之一。本文综述了护理实习生手卫生重要性、现状以及医院管理护理实习生手卫生的各种举措, 以期为医院手卫生管理提供依据。)